Saving Face : The Emotional Costs of the Asian Immigrant Family Myth - Chung, Angie Y., 1973- (Book collections on Project MUSE., 2016)
The Asian immigrant family myth celebrates Asian families for upholding the traditional heteronormative ideal of the "normal (white) American family" yet also demonizes them for reinforcing oppressive and backwards cultural values. Saving Face cuts through these myths, offering a more nuanced portrait of Asian immigrant families in a changing world. Angie Y. Chung examines how the grown children of Korean and Chinese immigrants emotionally negotiate the complex and conflicted feelings they have toward their family responsibilities and upbringing through new modes of love, communication, and ca.